Artificial Intelligence: A Modern Approach - Russell, stuart J and Norvig, Peter (Dorlong Kindersley (India) Pvt. Ltdl, 2003)
Presents a guide to artificial intelligence, covering such topics as intelligent agents, problem-solving, logical agents, planning, uncertainty, learning, and robotics.